2015
DOI: 10.1105/tpc.15.00203
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Profiling of Developing Leaf and Shoot Apices Reveals Distinct Genetic and Environmental Control of Floral Transition and Inflorescence Development in Barley

Abstract: Timing of the floral transition and inflorescence development strongly affect yield in barley (Hordeum vulgare). Therefore, we examined the effects of daylength and the photoperiod response gene PHOTOPERIOD1 (Ppd-H1) on barley development and analyzed gene expression changes in the developing leaves and main shoot apices (MSAs) of barley by RNA sequencing. The daylength sensitivity of MSA development had two phases, floret primordia initiated under long and short days, whereas successful inflorescence developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
113
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 87 publications
6
113
0
Order By: Relevance
“…This indicated that Ppd-H1 and HvELF3 controlled the relative expression levels of BM genes under different ambient temperature conditions. HvBM3 and HvBM8 are known targets of Ppd-H1 under LD conditions and their expression patterns correlate with the development of the inflorescence (Digel et al, 2015(Digel et al, , 2016. In this study, we show that the effect of Ppd-H1 on HvBM3 and HvBM8 expression and flowering time was temperature dependent.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…This indicated that Ppd-H1 and HvELF3 controlled the relative expression levels of BM genes under different ambient temperature conditions. HvBM3 and HvBM8 are known targets of Ppd-H1 under LD conditions and their expression patterns correlate with the development of the inflorescence (Digel et al, 2015(Digel et al, , 2016. In this study, we show that the effect of Ppd-H1 on HvBM3 and HvBM8 expression and flowering time was temperature dependent.…”
Section: Discussionsupporting
confidence: 48%
“…The authors suggested an interaction between the photoperiod and thermosensitive pathway. Our study demonstrates that this interaction is mediated by Ppd-H1, which is functional under LDs, but not under SDs (Digel et al, 2015). Furthermore, we show that the effect of Ppd-H1 on early reproductive development under high temperatures is dependent on HvVRN1.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, in our experiments, Ppd-H1-dependent differences in leaf size were cumulative and increased with leaf number on the main stem. While Ppd-H1 does not have a strong effect on the vegetative-to-reproductive phase change, it strongly controls inflorescence development and stem elongation (Digel et al, 2015). Differences in the rate of leaf emergence, in the duration of leaf growth, and in the final leaf cell number suggested that Ppd-H1 affected leaf size by influencing the rate of agedependent progression of leaf development.…”
Section: Discussionmentioning
confidence: 98%